Transport properties of acceptor-doped barium zirconate by electromotive force measurements. (7th September 2016) - Han, Donglin; Noda, Yohei; Onishi, Takayuki; Hatada, Naoyuki; Majima, Masatoshi; Uda, Tetsuya
Abstract: In this work, a systematic work was performed to investigate the electrochemical transport properties of acceptor-doped BaZrO3 by measuring electromotive force on various gas concentration cells. For the measurements in the wet oxidizing atmosphere, where significant hole conduction occurs, the transport numbers of the ionic conduction were corrected by taking the effect of electrode polarization into consideration. The results revealed that regardless of whether Sc, Y, In, Ho, Er, Tm or Yb was doped, proton conduction predominated in the reducing atmosphere with the transport number close to unit. However, the contribution of ionic conduction weakens, and the contribution of hole conduction enhances, when the samples are exposed to the moist oxidizing atmosphere. In addition, introducing Ba-deficiency results in degraded electrochemical conductivity, but the transport number in either the moist reducing or the moist oxidizing atmosphere does not change obviously. Highlights: Almost pure proton conduction in acceptor-doped BaZrO3 in reducing atmosphere. Significant hole conduction in BaZrO3 doped with rare earth in oxidizing atmosphere. Negligibly small change in transport number with increasing Ba-deficiency. Consider electrode polarization effect for EMF method when hole conductive is high.